2014
DOI: 10.1108/jpbm-11-2013-0445
|View full text |Cite
|
Sign up to set email alerts
|

Market and brand-oriented schools of positioning

Abstract: Purpose – The purpose of this paper is to revise the concept of positioning to differentiate between fundamental approaches to it and chart a scheme of schools of positioning. Design/methodology/approach – An extensive literature review traces the roots and evolution of the concept. Two approaches to positioning are explored and related to the paradigms of market and brand orientation. Based on current theory and practice, different scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 94 publications
0
44
0
2
Order By: Relevance
“…Communications products applied by SMAN 10 Malang offers achievement and facilities. As the research findings conducted [7], they concluded that positioning is a key concept in marketing, branding and strategy. This is supported by Kotler & Armstrong [8] which states that a good product is a product that is capable of describing himself as a salesman silence.Communication price set by SMAN 10 Malang relatively expensive for high school education.Communication presented a SMAN 10 Malang observed by researchers through observation showed that building visual store merchandising as claimed by Kotler & Armstrong [8], which are the devices to symbolize the typical school in accordance with the Leadership Academy program.SMAN 10 Malang is located at Jl.…”
Section: Formulation Of Marketing Communication Strategy and Its Implmentioning
confidence: 93%
“…Communications products applied by SMAN 10 Malang offers achievement and facilities. As the research findings conducted [7], they concluded that positioning is a key concept in marketing, branding and strategy. This is supported by Kotler & Armstrong [8] which states that a good product is a product that is capable of describing himself as a salesman silence.Communication price set by SMAN 10 Malang relatively expensive for high school education.Communication presented a SMAN 10 Malang observed by researchers through observation showed that building visual store merchandising as claimed by Kotler & Armstrong [8], which are the devices to symbolize the typical school in accordance with the Leadership Academy program.SMAN 10 Malang is located at Jl.…”
Section: Formulation Of Marketing Communication Strategy and Its Implmentioning
confidence: 93%
“…Kapferer (2012) coined the phrase "brand as product", with the logic being that one cannot choose to ignore the brand as it is an integral part of the product, and also one cannot ignore the ability of brand positioning strategies to create a personal and perhaps powerful consumer-brand bond. Urde and Koch (2014) define "brand positioning as an inside-out approach that defines and implements an intended position with brand perception as its point of departure and continuing frame of reference". Dwelling further, brand positioning refers to "a consumer level perception of the brand and is based on the subjective attributes and images the consumers have about the brand in their memory structure".…”
Section: Brand Positioning Strategiesmentioning
confidence: 99%
“…Dwelling further, brand positioning refers to "a consumer level perception of the brand and is based on the subjective attributes and images the consumers have about the brand in their memory structure". There are various ways of enveloping consumer response and one of them is to adopt an inside-out approach (Urde & Koch, 2014), and the second way is the adoption of an external, outsidein approach, which implies that and individual relies on the attributes of market mavens to gather valuable market information.…”
Section: Brand Positioning Strategiesmentioning
confidence: 99%
“…O posicionamento de marca tem sido definido como projetar determinada marca/serviço na mente do público-alvo, buscando ocupar um lugar distintivo (Ries & Trout, 1982;Kotler, Keller & Lu, 2009 (Urde & Koch, 2014;Lazarin & Slongo, 2015). Em geral, nos mercados de serviços há grande quantidade de competidores, diferentes tipos de ofertas de serviços e reduzidas barreiras para novos entrantes (Fitzsimmons & Fitzsimmons, 2014).…”
Section: Introductionunclassified